EVALUASI EFEKTIFITAS PENERAPAN KONSEP MANAJEMEN PROYEK PADA PELAKSANAAN PROYEK PELEBARAN JALAN MENAMBAH LAJUR BATAS KABUPATEN KAMPAR-BATAS KOTA BANGKINANG - Islah, Muhammad; Adeswastoto, Hanantatur; Wahyudi, Wahyudi; Rantisi, Alib Jabsyam; Zahara, Della; Janna, Miswatun (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
In construction project activities, planning is used as a reference material for project management and become a standard for project implementation which includes: cost factors, time factors and closely related quality factors on project performance. This research is limited to the scope of physical activities/construction stages with objectives to evaluate the effect of the effectiveness of applying project management concepts on project implementation road construction in terms of cost, time and quality on project performance. In the context of a road construction project in Kampar Regency, this research aims to evaluate the effectiveness of applying project management concepts in improving project performance. This research also analyzes the influence of cost, time and quality factors on overall project performance. Using a multiple linear regression approach, the research results show that cost and time factors have a positive and significant influence, while quality factors have a smaller contribution to improving project performance. This research uses a qualitative and quantitative descriptive approach with multiple linear regression analysis methods. Therefore, the results obtained will depend on primary data collected through questionnaires and interviews. This research can help in identifying and managing risks associated with project implementation, thereby minimizing delays and additional costs. Keywords: cost factor, time factor, quality factor, validity test, linear regression model.